PENGENDALIAN BADAN LINGKUNGAN HIDUP (BLH) KOTA PEKANBARU TERHADAP PENCEMARAN SUNGAI SIAK RUAS KOTA PEKANBARU - Juhar, Syahrial; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Siak river water quality degradation segment Pekanbaru due rampant pollution andlandfill waste by communities living area Siak river, the state cange Siak river is no longer fitfor use as a community activity area Siak river flow.There are some constraints Environment Agency in Pekanbaru, controlling riverpollution such as lack of human resources skilled in the art, the lack of support facilities thatare used to monitor and control the Siak river.Researchers used theoretical concept is composed of a control concept, settingstandards, measuring and comparing the performance, take corrective action. This study usedqualitative research methods to the assessment of descriptive data.In collecting the data, the researcher used interview techniques, observation andstudy of literature. By using key informant and the informant as a supplementary source ofinformation.These results indicate that not maximal Siak river pollution control implementation iscarried out by the Environment Agency in Pekanbaru. It is evident the absence of changes inwater quality of the river towards yan g better, and there are many pollution due to industrialwaste and garbage disposal are carried out by people who live Siak river basin area.Keywords : Pollution, Control, Siak River Segment Pekanbaru.